PERIPHERAL OSTEOMA OF MANDIBLE - A CASE REPORT AND ANALYSIS OF LITERATURE - Elitsa G.Deliverska (Peytchinski Publishing, 2016)
Background Osteoma is a benign osteogenic tumor arising from the proliferation of cancellous or compact bone. The osteoma can be central, peripheral or of an extraskeletal type. Objective: The purpose of our paper is to present a case of peripheral osteoma of the mandible and to evaluate the diagnosis and management of osteoma of the maxillofacial region with an analysis of the literature. Material and Methods: We present a 68 years old female patient with a hard, well defined swelling on the left side of the mandible in vestibular aspect near to the lower margin and medial to the angle. Results: Clinical evaluation (extraoral and intraoral) of patient and radiological findings directs for a diagnosis- peripheral osteoma of left side of mandible and the patient was scheduled for surgical treatment. Conclusion: Peripheral osteoma of the jaw bones is uncommon. The post surgical follow-up should include periodic clinical and radiographic studies. Patients with osteoma associated with impacted or supernumerary teeth should be evaluated for possible Gardner's syndrome.